Drink and be merry [videorecording (DVD)] - Winters, Leon; White, Jefferson (Actor); Zucker, Sophie; Hogan, Siobhan Fallon (X4 Pictures, 2025)
Over the nights before Christmas, the young bartender of a struggling NYC dive, must balance caring for his misanthropic, aging regulars who rely on him for far more than pouring drinks with his desires to muster some Christmas spirit.